A Community Service Program: Online Basic Training on Remote Sensing Image Interpretation for Public Participation in Monitoring Marine Environmental Damage - Luhur Moekti Prayogo; Intan Septarina (Community Service: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
The use of remote sensing as a means of coastal environmental education is a strategic approach to increase public literacy about the condition of marine ecosystems that are vulnerable to damage. This community service activity aims to introduce the basics of satellite image interpretation to participants from various coastal areas of Indonesia through online training which will be held on November 8, 2025 with a total of 30-50 participants for free. The training is designed using an experiential learning approach so that participants can learn concepts and practice them directly through online platforms. The material included an introduction to the basic principles of remote sensing, visual interpretation techniques, the use of a combination of image bands, and the application of satellite imagery to detect changes in mangrove cover. The results of the training showed a significant increase in scores in all competency categories after the training. Before training, the score is in the range of 25–40%, while after training it increases to around 70–80%. This indicates that the training is effective in improving the participants' understanding and skills in all aspects measured. In addition, online learning methods are quite effective in encouraging collaborative interaction across regions. This program shows that remote sensing technology can be simplified into educational materials that are easy for the public to understand.